Camel milk whey hydrolysate inhibits growth and biofilm formation of Pseudomonas aeruginosa PAO1 and methicillin-resistant Staphylococcus aureus. (May 2020) - Abdel-Hamid, Mahmoud; Romeih, Ehab; Saporito, Paola; Osman, Ali; Mateiu, Ramona Valentina; Mojsoska, Biljana; Jenssen, Håvard
Abstract: Pseudomonas aeruginosa PAO1 and Methicillin-Resistant Staphylococcus aureus (MRSA) are amongst the most virulent pathogens, causing chronic and life-threatening human infections. Thus, novel natural compounds able to inhibit these pathogens, reduce and/or eradicate their biofilms are in high demand. Camel milk has been demonstrated to contain many functional and bioactive molecules and has consequently been considered in various therapeutic applications. This study aimed to assess the antibacterial and antibiofilm activities of the camel milk whey proteins after hydrolysis by papain, and the obtained fractions from size exclusion chromatography (SEC) against PAO1 and MRSA. Antibacterial activity of camel milk whey against PAO1 and MRSA was enhanced by hydrolysis with papain. Size-exclusion fraction 2 (SEC-F2) had significantly ( P < 0.01) the highest antibacterial activity against PAO1 and MRSA with a minimum inhibitory concentration of 0.156 and 0.3125 mg/mL, respectively. Additionally, SEC-F2 significantly ( P < 0.01) decreased the biofilm biomass by 60.45% and 85.48% for PAO1 and MRSA, respectively. Moreover, SEC-F2 potentially reduced the PAO1 and MRSA biofilms depending on its concentrations. Scanning electron microscopy showed that the SEC-F2 fraction caused potential morphological changes in both PAO1 and MRSA, mostly represented in cell elongation and leakage of cytoplasmic content. In conclusion, this study has demonstrated that hydrolysis of camel milk whey with papain generates robust antibacterial and antibiofilm small-peptides against PAO1 and MRSA. Highlights: Hydrolysis of camel milk whey by papain enhanced the antibacterial activity against PAO1 and MRSA. Size exclusion chromatography fraction 2 (SEC-F2) exhibited the highest antibacterial activity. SEC-F2 inhibited the formation of the biofilm by PAO1 and MRSA. SEC-F2 eradicated the biofilm formed by PAO1 and MRSA.